A New Current-Mode Log and Antilog Amplifier using Current Follower Transconductance Amplifier (CFTA) - Hamad, Amira R; Abdulla, Azad N (Zanco Journal of Pure and Applied Sciences, 2024)
Log and Antilog Amplifiers are two very important functions in many electronic devices. Thus, in this article a new current mode (CM) log and antilog amplifier using current follower transconductance amplifier (CFTA) are presented. The logarithmic circuit is constructed using only one CFTA as active elements and one metal oxide semiconductor (MOS) transistor as diode operation and antilogarithmic amplifier circuit is implemented using only one CFTA as the active component, one MOS transistor as diode operation and two MOS transistor as active resistors. It provides the advantage of using MOS transistor instead of a resistor and diode that is beneficial to IC implementation in terms of space consideration which are suitable for IC implementation. These circuits provide logarithmic and antilogarithmic responses. Additionally, there is no demand to set selection criteria for components. The operation of the circuit in the current mode was verified by a non-ideality study. PSPICE was used to test the scheme's functioning. The output curves coincide very close with the theoretical expectation.